2010
DOI: 10.1021/ie100527x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Toluene and 1,2,4-Trimethylbenzene over ZSM-5 and Mordenite Catalysts: A Comprehensive Kinetic Model with Reversibility

Abstract: The catalytic transformations of toluene, 1,2,4-trimethylbenzene (TMB), and an equimolar mixture of the two compounds were investigated over H-mordenite and H-ZSM-5 catalysts. A series of experiments were conducted in a riser simulator over a temperature range of 300−400 °C and reaction times of 5−20 s. The influence of reaction conditions on variation of 1,2,4-TMB conversion, toluene conversion, para- to ortho-xylene ratio, xylenes to TMB isomers ratio, 1,3,5-TMB to 1,2,3-TMB ratio, and xylenes to benzene rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Xylene isomerization, disproportionation, and dealkylation are catalyzed by Brønsted acid sites [6][7][8]. Disproportionation needs higher concentrations of acid sites [9] and the strength of these sites follows the trend: isomerization < dealkylation < disproportionation [10,11]. The acidity of zeolites is determined by their Si/Al ratio, with the total number of acid sites decreasing with increasing Si/Al ratio due to the lower amount of Al [2,5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Xylene isomerization, disproportionation, and dealkylation are catalyzed by Brønsted acid sites [6][7][8]. Disproportionation needs higher concentrations of acid sites [9] and the strength of these sites follows the trend: isomerization < dealkylation < disproportionation [10,11]. The acidity of zeolites is determined by their Si/Al ratio, with the total number of acid sites decreasing with increasing Si/Al ratio due to the lower amount of Al [2,5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] However, it was found that medium-pore zeolites, like ZSM-5, have a higher selectivity towards p-xylene. Firstly, the pores need to be large enough for the diffusion of the bulky TMB species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that 12-membered rings have a higher catalytic activity than 10-membered rings due to their enhanced diffusion capacity. [13][14][15] However, it was found that medium-pore zeolites, like ZSM-5, have a higher selectivity towards p-xylene. [16,17] Secondly, the reaction pathway taking place depends on the acid site strength.…”
Section: Introductionmentioning
confidence: 99%
“…One of these processes with high potential of deactivation is the disproportonation (DP) of toluene and/or transalkilation (TA) of C 9 aromatics and toluene to C 8 aromatics over zeolites in fixed-bed reactors. DP and TA involve solid-acid catalytic processes which occur over medium-pore zeolites, such as ZSM-5, and large-pore zeolites, such as mordenite, Beta, and Y [1][2][3][4]. For H-mordenite, the temperature is a dominant factor that determines the activity and coking tendency, as the undesired reaction, due to its one-dimensional channel system [5].…”
Section: Introductionmentioning
confidence: 99%
“…In these models, however, many simplified conditions have been assumed. Most of these models have been conducted at the laboratory scale under certain conditions with applying no dynamic data [1][2][3][4][5][6][7]12]. Additionally, online investigation of the industrial reactors' parameters (e.g., catalyst deactivation, conversion, product…”
Section: Introductionmentioning
confidence: 99%